Antibacterial Action of Jineol Isolated from Scolopendra subspinipes mutilans against Selected Foodborne Pathogens - Bajpai, Vivek K.; Shukla, Shruti; Paek, Woon K.; Lim, Jeongheui; Kumar, Pradeep; Na, MinKyun (Frontiers in Microbiology, 2017)
Abstract This study was undertaken to assess the antibacterial potential of 3,8-dihydroxyquinoline (jineol) isolated from Scolopendra subspinipes mutilans against selected foodborne pathogens E. coli O157:H7 and S. aureus KCTC-1621. Jineol at the tested concentration (50 µL; corresponding to 250 µg/disc) exhibited significant antibacterial effects as a diameter of inhibition zones (11.6-13.6 mm), along with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values found in the range of (62.5-125 µg/mL) and (125-250 µg/mL), respectively. Jineol also exhibited significant antibacterial effects as confirmed by the reduction in bacterial cell viabilities, increasing release of potassium (K+) ions (650 and 700 mmole/L) and 260 nm materials (optical density: 2.98-3.12) against both the tested pathogens, E. coli O157:H7 and S. aureus KCTC-1621, respectively. Moreover, changes in the cell wall morphology of E. coli O157:H7 and S. aureus KCTC-1621 cells treated with jineol at MIC further confirmed its inhibitory potential against the tested pathogens, suggesting its role as an effective antimicrobial to control foodborne pathogens.